Histopathological changes that induced by Monsodium glutamate and Sodium nitrite on the eyes of white mice Mus musculus and the protective role of Grape seeds oil - Sanabel Al-Thanoon; ali ashgar (College of Education for Pure Sciences, 2021)
Current study tackled potency of MSG and NaNO2 to induce histopathological changes in eye texture of Swiss-mice and protective role of grape seed-oil against toxicity these substances may cause. In this study, 36 adult mice divided into six groups with control. One group was dosed with MSG at 9g/kg; another was injected with NaNO2 at 110mg/kg for two months, groups with interference of two substances, and two groups with interference of grape seeds-oil with each substance. Results showed emergence of histopathological lesions. In treatment with MSG, there was wide destruction and damage to photoreceptor cells and outer, inner nuclear layer, separation corneal stroma and gliosis in optic nerve. In treatment with NaNO2, damage was extensive in components of eye; it was noted the appearance of roseat pattern in outer, inner nuclear layer, necrosis of outer plexus layer and contraction of lens fibres. When treating with an interference of MSG and NaNO2, damage was observed to the surface epithelial tissue of cornea, stroma fibres, reduction in fibroblasts, necrosis in some cells of ciliary body, and in retina extensive damage was observed in its layers. When treating by MSG with oil, increase in the inner plexus vasa, nerve fibres, and the inner nuclear layer was observed and slight damage to the outer pieces of the photoreceptors. When treating with NaNO2, oil, infiltration of inflammatory cells appeared in the ganglion cells, increased vasa, edema and hyperplasia in the epithelium of the lens.